O modelo sueco e o pleno emprego: a crise da década de 1990 - Viana, Alexandre Guedes (2007)
During the 1930s and 1940s, the Swedish State introduced a set of measures that had as goals reducing the unemployment, raising the economic growth and increasing the welfare. However, this set of measures was blocked by challenges that appeared after the World War II, specially the conflict between inflation and unemployment. To solve this conflict, the economists Gösta Rehn and Rudolf Meidner presented in 1951 an economic model that has been recognized as the synthesis of the Swedish model. This model reveals as an alternative for the economic policy management, therefore it has as objective to reach the full employment and the price stability simultaneously, using labour market policies and a restrictive fiscal policy. These objectives had been reached from the middle of 1950s until the beginning of 1990s, period when Sweden faced a hard economic crisis. One of the crisis consequences was the sharply unemployment rising rates, which raised questions about the validity of the model. Thus, the aim of this paper is to introduce the Swedish model and the full employment issue, analyzing the unemployment rising rates after the 1990s crisis. To reach this aim the theoretical aspects of the Swedish model are discussed, as well as the macroeconomic policies adopted by Sweden after the World War II and the reasons for the unemployment rising rates. This is a worthy issue because the Swedish model was efficient in maintain the full employment for almost four decades